Soil and crop contamination through wastewater irrigation and options for risk reduction in developing countries - Abaidoo, Robert C.; Keraita, Bernard N.; Drechsel, Pay; Dissanayake, Priyanka; Maxwell, Akple S. (2010)
Wastewater irrigation is becoming a global phenomenon, as a result of global water scarcity and increased pollution of water sources. While this practice offers many opportunities, human health risks from contaminated soils and crops irrigated with wastewater pose the greatest challenges to this practice. In this chapter, contaminants in wastewater of most relevance to soil and crop, such as pathogens, heavy metals and other organic contaminants as well as the related human health and environmental risks are discussed. There is a general consensus that untreated wastewater contaminates soils and crops and poses health risks, however the threats vary widely. While wastewater treatment is the best choice to address this problem, a number of low-cost technological options and health protection measures exist to address the contamination challenges especially in developing countries. These include irrigation methods, farm-based measures for improving water quality, choice of crop, water application techniques, soil phytoremediation, zoning and post-harvest measures. For comprehensive risk reduction, a combination of these measures is recommended especially where comprehensive wastewater treatment is not feasible.